The TRIVIA Cohort for Surgical Management of Tetralogy of Fallot: Merging Population and Clinical Data for Real-World Scientific Evidence - Samuel Blais, BSc; Ariane Marelli, MD, MPH; Alain Vanasse, MD, PhD; Nagib Dahdah, MD; Adrian Dancea, MD; Christian Drolet, MD; Frederic Dallaire, MD, PhD (CJC Open, 2020)
Background: Guidelines for surgical management of tetralogy of Fallot (TOF) are often based on low-quality evidence due to the many challenges of congenital heart disease: heterogeneous cardiac anatomy, consequences from surgical interventions arising years later, and scarcity of hard outcomes. The overarching goal of the Tetralogy of Fallot Research for Improvement of Valve replacement Intervention: A Bridge Across the Knowledge Gap (TRIVIA) study is to evaluate the long-term impact of the surgical management strategies in TOF. The specific objectives are: (1) to describe the long-term outcomes of TOF according to the native anatomy and the presence of genetic conditions, (2) to evaluate the long-term outcomes of surgical repair according to associated residual lesions, and (3) to evaluate the impact of paediatric pulmonary valve replacements on the long-term outcomes. Methods: The TRIVIA study is a population-based cohort including all subjects with TOF in the province of Québec between 1980 and 2017. It links patient-level granular clinical data with long-term administrative health care data. We will evaluate mortality, cardiovascular interventions, and hospitalizations for adverse cardiovascular events using survival Cox models and marginal mean/rates models for recurrent events, respectively. Multivariate multilevel models will correct for potential confounders, and risk score matching will mitigate the potential of confounding by indication. Results: The current TRIVIA cohort includes 1001 eligible subjects with TOF with complete lifelong follow-up for > 98%. The median follow-up is 17.1 years, totalling > 17,000 patient-years. Conclusions: Universal health insurance data combined with granular clinical data enable the development of population-based cohorts, to which contemporary statistical methods are applied to address important research questions in congenital heart disease research. Résumé: Contexte: Les lignes directrices pour la prise en charge chirurgicale de la tétralogie de Fallot (TdF) sont souvent basées sur des données de faible qualité en raison des nombreux défis posés par les maladies cardiaques congénitales : anatomie cardiaque hétérogène, répercussions des interventions chirurgicales survenant des années plus tard et rareté de conclusions solides. L'objectif principal de l’étude TRIVIA (Tetralogy of Fallot Research for Improvement of Valve replacement Intervention: A Bridge Across the Knowledge Gap) est d'évaluer l'impact à long terme des stratégies de prise en charge chirurgicale dans les TdF. Les objectifs spécifiques sont les suivants : (1) décrire les issues à long terme de la TdF en fonction de l'anatomie native et de la présence de conditions génétiques, (2) évaluer les conséquences à long terme de la chirurgie réparatrice en fonction des lésions résiduelles associées, et (3) évaluer l'impact des remplacements valvulaires pulmonaires pédiatriques sur le pronostic à long terme. Méthodes: L'étude TRIVIA est une étude de cohorte basée sur une population comprenant tous les sujets atteints de TdF dans la province du Québec entre 1980 et 2017. Elle fait le lien entre les données cliniques détaillées des patients et les données administratives des soins de santé à long terme. Nous évaluerons la mortalité, les interventions cardiovasculaires et les hospitalisations pour troubles cardiovasculaires en utilisant respectivement des analyses de survie par les modèles de Cox et des modèles de moyennes/taux marginaux pour les événements récurrents. Des modèles multivariés à plusieurs niveaux permettront de corriger les facteurs de confusion potentiels, et l'appariement par des scores de risque atténuera le potentiel de confusion par indication. Résultats: La cohorte de l’étude TRIVIA comprend actuellement 1001 sujets admissibles atteints de TdF avec un suivi complet tout au long de la vie pour > 98 %. Le suivi médian est de 17,1 ans, pour un total de > 17 000 patients-années. Conclusions: Les données de l'assurance maladie universelle combinées à des données cliniques détaillées permettent la mise en place de cohortes populationnelles, auxquelles les méthodes statistiques contemporaines pourront être appliquées afin de répondre aux questions importantes pour la recherche portant sur les maladies cardiaques congénitales.